HUBUNGAN TINGKAT DEPRESI TERHADAP PERILAKU ANTISOSIAL PADA REMAJA - Julvan; P. Sihombing, Yan; O. Siagian, Laura (Jurnal Kedokteran Methodist, 2021)
Background: Depression is a state of decreased life function of a person associated with feelings of sadness and helplessness that lasts for at least 2 weeks, this decline in life functions can result in a person unable to carry out his daily activities properly. Globally, more than 264 million people experience depression at various ages. Depression in adolescents is prone to occur due to many adjustments to the environment and various existing life stressors, if this lasts for a long time without attention from people around, then over time it will cause a persistent antisocial behavior disorder and can affect antisocial personality in adulthood. The purpose of this study was to determine the relationship between depression levels and antisocial behavior in adolescents. Methods: The research used literature review method using secondary data. Data were collected using documentation techniques. Documentation was obtained from search results on Google Scholar and PubMed within the last 10 years of publication. Results: There are 15 journals that match the research variables and inclusion criteria. From this study, it was found that there was a relationship between depression level and antisocial behavior in adolescents (p < 0.05). Conclusion: There is a relationship between the level of depression on antisocial behavior in adolescents.